External ear malformations and cardiac and renal anomalies: A systematic review and meta-analysis. - Arman Ghafari; Leonardo Alaniz; Cindy Vu; Alejandra Ibarra; Medha Vallurupalli; Sierra Willens; Justin Cordero; Miles J Pfaff (PLoS ONE)
Context External Ear Malformations (EEM) continue to be a common malformation seen in the pediatric patient population. This study aims to further elucidate the correlation between EEM and cardiac and renal anomalies. Objective A systematic review and meta-analysis to study the incidence of cardiac and renal anomalies associated with syndromic and isolated (EEM). Data sources The literature search spanned multiple databases, including Google Scholar, PubMed, Scopus, Web of Science, and MEDLINE. Study selection Studies must be focused on EEM and cardiac and/or renal anomalies. Only articles written in English were included. Data extraction General study characteristics, number of EEM patients, number of cardiac and renal anomalies and whether cases were syndromic were extracted from the studies. Results Of 1,058 initial studies, 33 were included for meta-analyses. Mean JBI score for all included studies was 92.06%, indicating acceptable study quality. Interrater reliability was high, with a Cohen kappa score for all studies of 0.94. The resulting pooled prevalence of cardiac abnormalities was 20% [95% CI:13-28%], while renal abnormalities were 13% [95% CI: 7-20%]. The most common anomalies were VSD (3.725%) and renal agenesis (2.04%). The presence of syndrome data across studies was not a significant modifier of prevalence rates. Limitations Primary limitation is due to heterogeneity in individual study methodology and reporting standards. Conclusions These results highlight a higher prevalence of cardiac-related conditions than renal anomalies in patients with both syndromic and non-syndromic EEM in the included studies, underscoring the need for thorough clinical evaluations.